Cultural Dimensions of Symbols Style and Power Artifactual Communication in Abdul Muhaimin Iskandar Declaration Video - Maskuri, M. Ibnu Naufal; Daulay, Hamdan; Rifa'i, Akhmad; Ridho, Ali; Tahrus, Zainun Nur Hisyam (Titian: Jurnal Ilmu Humaniora, 2026)
Abdul Muhaimin Iskandar is a national political figure facing image challenges due to several controversies, such as the "durian cardboard" corruption case, the decline of PKB's votes in the 2009 election, and conflicts with Gus Dur that resurfaced following statements by Yenny Wahid. Ahead of the 2024 presidential election, he seeks to reconstruct his political image through nonverbal communication in his declaration video. This study analyzes the content of the political declaration, the forms of artifactual communication, and positive image building strategies. Using a qualitative approach and Ferdinand de Saussure’s semiotic theory, the study found that the artifactual communication employed falls under symbolic practices (practical artifacts), which convey emotional information, behavior, and identity differentiation. To build a positive image, a low-fashion strategy is used to portray simplicity, closeness to the people, and cultural ties with Nahdliyin voters. This strategy serves as an important tool for constructing political symbols that strengthen identity and effectively gain public sympathy. Abstrak Abdul Muhaimin Iskandar adalah tokoh politik nasional yang menghadapi tantangan citra akibat beberapa kontroversi, seperti kasus korupsi "karton durian", penurunan perolehan suara PKB dalam pemilihan umum 2009, dan konflik dengan Gus Dur yang kembali mencuat setelah pernyataan Yenny Wahid. Menjelang pemilihan presiden 2024, ia berupaya membangun kembali citra politiknya melalui komunikasi nonverbal dalam video deklarasinya. Studi ini menganalisis isi deklarasi politik, bentuk-bentuk komunikasi artefaktual, dan strategi membangun citra positif. Dengan menggunakan pendekatan kualitatif dan teori semiotika Ferdinand de Saussure, studi ini menemukan bahwa komunikasi artefaktual yang digunakan termasuk dalam praktik simbolik (artefak praktis), yang menyampaikan informasi emosional, perilaku, dan diferensiasi identitas. Untuk membangun citra positif, strategi busana sederhana digunakan untuk menggambarkan kesederhanaan, kedekatan dengan rakyat, dan ikatan budaya dengan pemilih Nahdliyin. Strategi ini berfungsi sebagai alat penting untuk membangun simbol politik yang memperkuat identitas dan secara efektif mendapatkan simpati publik.